ANALISIS IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) BARANG MILIK DAERAH - Supriyanto, Supriyanto (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2015)
After the enactment of Law No. 23 of 2014 on Regional Government, and Government Regulation No. 27 of 2014 on the Assets Management of State/Regions, each region must be manage its assets in an orderly administration, the rule of law, and physical order. To facilitate the local government in assets management, has been developed the Regional Management Information System-Regional Assets (SIMDA-BMD). Local government of Banjarnegara has implemented SIMDA-BMD since 2009. This paper discusses the analysis of the implementation of SIMDA-BMD on Local government of Banjarnegara. The purpose of this paper is to determine how SIMDA-BMD process data into information, internal controls have been applied, and the characteristics of the quality of information produced. The result of this paper, it SIMDA-BMD is good in processing data becomes information and internal control that is applied is sufficient. The information quality produced by SIMDA-BMD is meet the relevant quality characteristics, but has not completely reliable because the book value is equal to the purchase price, it is because SIMDA-BMD does not have the depreciation facility.